2021
DOI: 10.18433/jpps31417
|View full text |Cite
|
Sign up to set email alerts
|

High-quality reports and their characteristics in the Japanese Adverse Drug Event Report database (JADER)

Abstract: Purpose: Spontaneous adverse drug reaction reporting is the foundation of postmarketing drug safety monitoring. The present study aimed to analyze and clarify the quality and characteristics of the Japanese Adverse Drug Event Report database (JADER) using the World Health Organization (WHO) documentation grading scheme and the vigiGrade completeness score. The characteristics of reports were described using both schemes simultaneously. The way of proper use of these two schemes was explored. Methods: The WHO d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In contrast, reports from PRHs and other HCPs (including regulatory affairs officers, clinical trial associates, nurses, and medical assistants) were flagged as the key features negatively associated with Malaysian report completeness ( Figure 2 B). These findings are consistent with the features observed in the United States [ 15 ], Brazil [ 16 ], Spain [ 17 ], South Korea [ 18 ], and Japan [ 19 , 20 ]. Of note, the NPRA classified the reports from PRHs as reported by other HCPs when the primary reporter was unknown.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, reports from PRHs and other HCPs (including regulatory affairs officers, clinical trial associates, nurses, and medical assistants) were flagged as the key features negatively associated with Malaysian report completeness ( Figure 2 B). These findings are consistent with the features observed in the United States [ 15 ], Brazil [ 16 ], Spain [ 17 ], South Korea [ 18 ], and Japan [ 19 , 20 ]. Of note, the NPRA classified the reports from PRHs as reported by other HCPs when the primary reporter was unknown.…”
Section: Discussionsupporting
confidence: 90%
“…The number of reports on ADRs in the JADER has been increasing yearly; however, most reports are from companies, while those from medical institutions are few. Tsuchiya et al 24 . demonstrated that of 561 122 ADR reports in the JADER, 419 540 (98.1%) were reported by pharmaceutical companies and 8257 (1.9%) were reported by medical institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that the number of ADR reports submitted by pharmacists significantly increased with an increase in the number of hospitals charging an additional fee for pharmacist-performed ward operations. [22][23][24] It was suggested that the implementation of ward-based clinical pharmacy services provides clinical pharmacists with opportunities to encounter more ADRs and enhances cooperation between pharmacists handling drug information services and those handling ward operation services. Thus, posting pharmacists at wards and providing drug-related information could be effective in promoting ADR reporting.…”
Section: Discussionmentioning
confidence: 99%